CIRC Model with Animated Video Support for Improving Anecdotal Text Writing - Nur Aulia Harahap; Asri Yulianda; Saprida (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to determine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model supported by animated videos in enhancing students’ skills in writing anecdotal texts. Employing a quasi-experimental one-group pretest-posttest design, the research involved 35 Grade X students at the high school level. Data collection was carried out through writing tests administered before and after the implementation of the learning model. Descriptive statistics, normality testing, and a paired sample t-test were used to analyze the data. The findings revealed a notable improvement in students' writing performance. The average score increased from 65.2 in the pretest to 82.5 in the posttest. Additionally, the minimum score rose from 55 to 70, and the maximum score increased from 75 to 92. The paired sample t-test produced a t-value of -12.45 and a p-value of 0.000 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. These results suggest that the integration of the CIRC model and animated videos fosters better understanding of anecdotal text structure and enhances students' engagement and creativity in writing. The multimedia element appears to facilitate deeper comprehension and active participation. Based on these outcomes, the CIRC learning model with animated video support is recommended as an innovative pedagogical strategy for teaching anecdotal writing in Indonesian language classes at the senior high school level.